2005
DOI: 10.1002/cncr.21470
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory molecule B7‐H1 in primary and metastatic clear cell renal cell carcinoma

Abstract: BACKGROUNDCancer cell expression of costimulatory molecule B7‐H1 has been implicated as a potent inhibitor of T‐cell–mediated antitumoral immunity. The authors recently reported that B7‐H1 is aberrantly expressed in primary renal cell carcinoma (RCC). Blockade of B7‐H1, as demonstrated in several murine cancer models, now represents a promising therapeutic target in RCC. However, the potential expression of B7‐H1 in metastatic RCC has not been investigated. In the current study, the authors updated their prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 56 publications
(43 reference statements)
12
116
2
Order By: Relevance
“…As in our prior B7-H1 studies (18,19), the association of tumor expression of B7-H4 with RCC progression and patient survival may have important implications for future therapy. Systemic IL-2 immunotherapy was the first Food and Drug Administration-approved treatment for metastatic RCC.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As in our prior B7-H1 studies (18,19), the association of tumor expression of B7-H4 with RCC progression and patient survival may have important implications for future therapy. Systemic IL-2 immunotherapy was the first Food and Drug Administration-approved treatment for metastatic RCC.…”
Section: Discussionmentioning
confidence: 66%
“…Specifically, we have demonstrated that aberrant RCC expression of the negative costimulatory ligand B7-H1 has been associated with increased disease progression and decreased cancer-specific survival (18,19). To date, however, studies pertaining to RCC tumor expression of B7-H4 have not been performed.…”
mentioning
confidence: 99%
“…Indeed, the expression of PD-L1 is associated with reduced survival and an unfavorable prognosis in a number of cancers, including lung (10), renal (11)(12)(13), pancreatic (14)(15)(16), and ovarian (17). In contrast, the levels of tumor-infiltrating lymphocytes, and more specifically cytotoxic T cells, have been correlated with improved prognosis in a number of cancers (18).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to broaden the investigation for immune status of the same examined cohorts, it further revealed that patients with higher levels of other immune checkpoints, such as CTLA-4 and LAG-3, were significantly correlated with longer survival. However, the result seems paradoxical when compared to the previous studies with the opposite finding that higher levels of these immune inhibitory molecules are associated with worse outcomes [8][9][10][11]. One hypothesis was that up-regulation of these immunomodulatory molecules might reflect an immune activation status driven by effector immune cells as a feedback mechanism for the prevention of immune-associated adverse damage.…”
Section: Commentarymentioning
confidence: 85%